Metaphor and Poetic Expression in the Poetry of Sri Aurobindo - Majumder, Rajib (International Journal of Applied and Scientific Research, 2024)
Renowned as a multifaceted figure in the 20th century, Sri Aurobindo engaged deeply in aesthetics, poetics, and Vedic and Upanishadic interpretations. His extensive writings spanned various disciplines, emphasizing the significance of literary discourse shaped by figurative thought in understanding human experience. This paper explores the pivotal role of metaphor in both common and literary discourse, offering a contemporary analysis of Sri Aurobindo's poetry. His philosophical contributions present an alternative to foundational ontological and epistemological assumptions in contemporary scientific thought. Using compelling metaphors, Sri Aurobindo illustrates the concealed depths of the mind and ego, comparing them to a temple crown emerging from waves. He envisions humanity as more than its conscious awareness, describing the momentary personality as a mere bubble on the vast ocean of existence. Sri Aurobindo's pursuit of elevated states of consciousness underscores his commitment to transformative exploration.